Koservasi dan Identifikasi Naskah Lontar Di Griya Agung Puri Tegaltamu Kabupaten Gianyar - Ni Nyoman Perni; I Made Dian Saputra; I Nengah Duija; I Wayan Sugita; I Made Wiradnyana; I Nyoman Temon Astawa; Made Iwan Indrawan Jendra; I Komang Aryadi Arnata; Ni Wayan Anik Ardiningsih; Luh Made Wardyaningsih; I Wayan Mardana Putra; Ni Ketut Yoni Riskayanti; Dewa Ayu Putu Winda Suari; Gusti Ayu Ary Purnami; Gede Rama Sudarsana; Ni Luh Putu Juliastini; Ni Putu Sumariani; I Kadek Nuryawan; I Wayan Putu Yasa; Putu Adi Darma Putra; I Ketut Putra Adi Utama (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Lontar is one form of ancient manuscripts (manuscripts) that exist in the archipelago. Lontar is commonly found on the island of Bali, especially in Griya Agung Puri Tegaltamu, Br. Tegaltamu, Batubulan Village, Sukawati District, Gianyar Regency is a priceless heritage. Therefore, it is necessary to preserve the manuscript through conservation activities and identification of both physical and content. Based on the results of the activities carried out on 49 lontar manuscripts. The identified characters can be classified into several types of text groups. Identification is obtained after all the lontar manuscripts are preserved and can be read clearly.